Characterization of the ToxB Gene from Pyrenophora tritici-repentis - J. Patrick Martinez; Sean A. Ottum; Shaukat Ali; Leonard J. Francl; Lynda M. Ciuffetti (Molecular Plant-Microbe Interactions, 2001)
The ToxB gene was cloned and characterized from a race 5 isolate of Pyrenophora tritici-repentis from North Dakota. ToxB contains a 261-bp open reading frame that encodes a 23 amino acid putative signal peptide and a 64 amino acid host-selective toxin, Ptr ToxB. Analysis of Ptr ToxB from heterologous expression in Pichia pastoris confirms that ToxB encodes a host-selective toxin.